Pitfalls in systemic-risk scoring - Benoit, Sylvain; Hurlin, Christophe; Pérignon, Christophe (Journal of Financial Intermediation, 2019)
In this paper, we identify several shortcomings in the systemic-risk scoring methodology currently used to identify and regulate Systemically Important Financial Institutions (SIFIs). Using newly-disclosed regulatory data for 119 US and international banks, we show that the current scoring methodology severely distorts the allocation of regulatory capital among banks. We then propose and implement a methodology that corrects for these shortcomings and increases incentives for banks to reduce their risk contributions.